Analisis Pengaruh Jarak dan Kondisi Pencahayaan terhadap Alat Deteksi Warna dengan Sensor TCS3200 Berbasis Arduino - Muhammad Ferdiyansyah; Yoga Putra Pratama; Emmidia Djonaedi (Pusat riset dan Inovasi Nasional, 2025)
The TCS3200 color sensor demonstrates limited accuracy under certain environmental conditions, particularly in relation to the distance between the sensor and the object, as well as the surrounding lighting. This study aims to investigate the effects of distance variation (0 cm, 2 cm, 4 cm, and 6 cm) and lighting conditions (bright and dark) on color detection using the TCS3200 sensor integrated with an Arduino microcontroller. An experimental method was employed, with color data converted into the CIELAB color space and analyzed using Delta E as the deviation indicator. The results indicate that the most accurate color readings occur at a distance of 0 cm, where the sensor receives maximum reflected light. Furthermore, measurements taken under dark conditions exhibit more consistent results compared to those under bright lighting, which tends to introduce optical interference. It can be concluded that the TCS3200 sensor performs best at close range and under controlled lighting conditions to ensure accurate and reliable color detection.